Interpathway regulation of the TRP4 gene of yeast. - Braus, G (1989)
Two regulatory proteins, PHO2 and the general control regulator GCN4, bind in vitro to the promoter of the tryptophan biosynthetic TRP4 gene; the TRP4 gene product catalyses the phosphoribosylation of anthranilate. PHO2 binds specifically to the TRP4 promoter, but does not bind to any other TRP promoter. PHO2 and GCN4 proteins bind in a mutually exclusive manner to the same sequence, UAS1, one of two GCN4 binding sites in the TRP4 promoter. UAS1 is the major site for GCN4-dependent TRP4 activation. The second GCN4 binding site, UAS2, interacts with GCN4 alone. PHO2 binding interferes with the general control response of TRP4 under low phosphate conditions and simultaneous amino acid starvation and thus the PHO2 regulatory protein connects phosphate metabolism and amino acid biosynthesis in yeast. The GCN4 protein mediates the response of the transcriptional apparatus to the environmental signal 'amino acid limitation', while PHO2 seems to be the phosphate sensor that adjusts the response to the availability of phosphate precursors.